Performance outcomes of supply chain agility: When should you be agile?. Issue 1 (31st October 2014) - Gligor, David M.; Esmark, Carol L.; Holcomb, Mary C.
Abstract: Traditionally, researchers have claimed agility as an attribute closely tied to the effectiveness of strategic supply chain management. Because of its association with customer effectiveness, some researchers have considered agility to be fundamentally different from lean, which has been linked to cost efficiency (Goldsby et al., 2006 ). Therefore, the relationship between agility and cost efficiency is not clear due to limited empirical scrutiny from researchers. Since elimination of waste is the cornerstone of lean, unraveling the relationship between agility and efficiency can also offer a better perspective on relationship between the fundamental paradigms of agility and lean. The manuscript makes a key contribution to the agility literature by examining the association between supply chain agility (FSCA), cost efficiency and customer effectiveness across various environmental situations. We use archival data to examine the moderating effects of environmental munificence, dynamism, and complexity. It has been argued that firms should embrace agile strategies when operating in highly uncertain environments, and embrace lean strategies when operating in more stable environments (Lee, 2002; Sebastiao and Golicic, 2008 ). We empirically question this premise to determine whether supply chain agility can also lead to superior performance for firms operating in stable environments. The study results also provide a better understanding of how FSCA contributes to firm financial performance. We evaluate the impact of FSCA on the firm's Return on Assets using archival data from the Compustat database. Thus, we provide evidence to managers that deploying resource to enhance FSCA can positively impact the firm's bottom line.